MONETARY POLICY AND ASSET PRICES IN BRAZIL: AN EMPIRICAL EVALUATION FOR THE PERIOD OF INFLATION TARGETING - Bejarano Aragón, Edilean Kleber da Silva (2018)
This paper investigates the reaction of the Central Bank of Brazil (CBB)’s monetary policy to stock and exchange rate price movements during the inflation-targeting period. In addition, it verifies whether the Selic rate has responded asymmetrically to the positive and negative deviations of asset price gaps. Therefore, different specifications of the CBB’s forward-looking reaction function are estimated by the Generalized Method of Moments. Results show that, in the short term, the CBB has responded asymmetrically to positive and negative exchange rate gaps, but that it has not reacted to stock price gaps. Moreover, the estimates of the implicit parameters of the reaction function indicate that only the long-term response of the Selic rate to expected inflation gap is significant. This is consistent with the theoretical analysis that the monetary authority should respond only indirectly to asset prices whenever such prices indicate changes in expected inflation.